1989
DOI: 10.1136/bmj.299.6705.953
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in consultation rates in urban general practice.

Abstract: Objective-To determine the patterns of consultations with the general practitioner among different ethnic groups and the outcome of these consultations.Design-Retrospective analysis of data from one urban group general practice collected during 1979-81 as part of a research project in seven practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(102 citation statements)
references
References 10 publications
4
96
1
1
Order By: Relevance
“…In England, native people were at a lower risk of developing allergic rhinitis than those born in Asia or the West Indies (272). Similarly, Maori people suffered more from allergic rhinitis than New Zealanders from English origin (273).…”
Section: Ethnic Groupsmentioning
confidence: 95%
“…In England, native people were at a lower risk of developing allergic rhinitis than those born in Asia or the West Indies (272). Similarly, Maori people suffered more from allergic rhinitis than New Zealanders from English origin (273).…”
Section: Ethnic Groupsmentioning
confidence: 95%
“…35 Consultation rates for mental disorders -in particular, anxiety and depressionhave been reported as lower in all immigrant groups in London general practices. 32 Once patients do attend their GP, there is evidence to suggest that patients coming from ethnic minorities are less likely to have mental health problems recognised, 36 and this has been shown particularly for black ethnic groups. 37 Lower anxiolytic prescribing has been reported in practices with more Asian names, 3 while a number of studies in the US have also reported that black Americans were prescribed fewer anxiolytics and hypnotics than white Americans.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Some studies have reported lower prevalence rates of anxiety symptoms in Caribbeans and black Africans, whereas in the Asian community, prevalence studies have produced conflicting findings. [27][28][29][30][31] Prevalence studies need to be interpreted with caution, as findings may be a function of differences in helpseeking behaviours and social beliefs about the acceptability and management of psychological illness 29,[32][33][34][35] or they may represent differences in the recognition of mental health problems by health professionals. [36][37] Cultural beliefs may deter patients from attending, particularly where family support is seen as the most appropriate coping method (for example, in the Bangladeshi community), or may hamper detection if, for example, alternative concepts are proffered such as belief in the role of magic (for example, in the Yoruba community).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…18 The most practical and efficient means reported in the literature of identifying a sample has been the use of general medical practices, 8,[19][20][21][22][23][24][25] especially as it has been estimated 26 that only 2% of 'black' and 'Asian' groups were not registered with a general practice in inner London. This approach circumvents the lack of a sampling frame needed for a random sample and the expense of using the address or electoral register to identify ethnic minority members.…”
mentioning
confidence: 99%